ANALYSIS OF BRIQUETTE QUALITY FROM OIL PALM FROND AND SHELL WASTE (Case Study of PT. Perkebunan Nusantara VII Unit Bekri) - Dewi, Septiana Kusuma; Mufti, Aulia Annas; Lisaftri, Yuni; Kurnianingtyas, Erlina (Sustainable Environmental and Optimizing Industry Journal, 2023)
Along with population growth in Indonesia which continues to increase, natural resources (SDA) experience a decrease in availability (energy crisis). Steps that can be taken to overcome e the energy crisis is to optimize the use of biomass energy as an alternative fuel. One of them is to take advantage of palm fronds and shell waste produced by PT. Perkebunan Nusantara VII Unit Bekri as charcoal briquettes. The process of making briquettes includes drying, carbonization, grinding, screening, and printing. The composition of the briquette raw material mixture consists of five variations, namely V1, V2, V3, V4, and V5. The purpose of this study was to analyze the quality of the briquettes based on testing the proximate value (moisture content, volatile matter content, ash content, and bound carbon content), calorific value, and the burning rate briquettes. The best results for the quality of briquettes from the use of waste palm fronds and shells were obtained in the V5 variation (50% fronds, 40% shells, and 1% adhesive), with a moisture content of 3,65% (SNI 8), volatile matter content of 25,30% (SNI 15), ash content of 6,68% (SNI 8), bound carbon content of 68,03%, calorific value of 6.281 (SNI 5.000), and burning rate of 0,00117 gr/s.